Membangun Hukum Yang Adil Dalam Bingkai Moralitas Pancasila - Noor Efendy; Ahmadi Hasan; Masyithah Umar (Sharia Journal and Education Center Publishing, 2023)
Abstract Pancasila is used in lawmaking or becomes a big step in making laws and regulations in accordance with the spirit of the Indonesian state which is humane, just, civilized and guarantees social justice for all Indonesian people. Therefore, an understanding of Pancasila justice needs to be done to provide a common perception of justice as the basis for the formation of good law. The research method used is normative research method in positive law with a focus on analyzing legal norms which are essentially prescriptive, specific provisions and tendencies in use. Using deductive logic analysis. The characteristics of justice based on Pancasila are the values of justice in the form of principles of justice, which fulfill certain principles or principles including the principle of justice based on faith in God Almighty. Promoting justice based on God's justice, the Pancasila principle of justice prioritizes human rights and humanizes humans as social beings whose justice must be protected, the Pancasila principle of justice upholds the values of solidarity and cohesiveness to create an atmosphere conducive to the nation, providing justice to Indonesian citizens, the Pancasila principle of justice adheres to the principle of deliberation for consensus through representation in order to create justice for citizens in expressing their respective opinions and the Pancasila principle of justice provides justice to all citizens without exception in accordance with applicable regulations. Keywords: Justice, Morality, Pancasila Abstrak: Pancasila digunakan dalam pembuatan undang-undang atau menjadi langkah besar dalam pembuatan peraturan perundang-undangan sesuai dengan semangat negara Indonesia yang manusiawi, adil, beradab dan menjamin keadilan sosial bagi seluruh rakyat Indonesia. Oleh karena itu, pemahaman tentang keadilan Pancasila perlu dilakukan untuk memberikan kesamaan persepsi tentang keadilan sebagai landasan terbentuknya hukum yang baik. Metode penelitian yang digunakan adalah metode penelitian normatif dalam hukum positif dengan fokus pada analisis norma hukum yang pada hakikatnya bersifat preskriptif, khusus ketentuan dan cenderungan digunakan. Menggunakan analisis logika deduktif. Ciri-ciri keadilan berdasarkan Pancasila adalah nilai-nilai keadilan yang berupa asas keadilan, yang memenuhi asas atau asas tertentu termasuk asas keadilan yang berdasarkan keimanan kepada Tuhan Yang Maha Esa. Mengedepankan keadilan berdasarkan keadilan Tuhan, Asas Keadilan Pancasila mengutamakan Hak Asasi Manusia dan memanusiakan manusia sebagai makhluk sosial yang keadilannya harus dilindungi, Asas Keadilan Pancasila menjunjung nilai nilai solidaritas dan kekompakan untuk menciptakan suasana yang kondusif bagi bangsa, memberikan keadilan kepada warga negara Indonesia, asas keadilan Pancasila menganut asas musyawarah untuk mufakat melalui perwakilan demi terciptanya keadilan bagi warga negara dalam mengemukakan pendapatnya masing-masing dan asas keadilan Pancasila memberikan keadilan kepada seluruh warga negara tanpa terkecuali sesuai dengan ketentuan yang berlaku. Kata Kunci: Keadilan, Moralitas, Pancasila